LEGAL REGULATION OF EXECUTIVE PROCEEDINGS: HISTORY, MODERNITY - Бородін, І. Л. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
In the article on the basis of the legislation (in historical and legal terms), the problems of legal and organizational support for the execution of court decisions (judges) in Ukraine are considered. As a result of the analysis of normative legal acts, proposals are made to improve the activity of the bodies (officials) of the executive service of Ukraine.